Design and Optimization of Vertical Axis Wind Turbines Using QBlade - Amani I. Altmimi; Mustafa Alaskari; Oday Ibraheem Abdullah; Ahmed Alhamadani; Jenan S. Sherza (Applied System Innovation, 2021)
Wind energy is considered one of the most important sources of renewable energy in the world, because it contributes to reducing the negative effects on the environment. The most important types of wind turbines are horizontal and vertical axis wind turbines. This work presents the full details of design for vertical axis wind turbine (VAWT) and how to find the optimal values of necessary factors. Additionally, the results shed light on the efficiency and performance of the VAWT under different working conditions. It was taken into consideration the variety of surrounding environmental conditions (such as density and viscosity of fluid, number of elements of the blade, etc.) to simulate the working of vertical wind turbines under different working conditions. Furthermore, the effect of the design factors was investigated such as the number and size of the blades on the behavior and performance of VAWT. It was assumed that the vertical wind blade works in different sites of Iraq. QBlade software (Version 8) was used to achieve the calculations and optimization processes to obtain the optimal design of vertical axis wind turbines that is suitable for the promising sites. The results proved that accurate results can be obtained by using QBlade software.